Social support in rural communities in Manabi province, Ecuador - Claudia Madrid Miles; Benjamin Bates; Sharon Casapulla; Mario Grijalva (James Cook University, 2022)
Introduction: Social support has been found in many contexts, and in urban Ecuador, to be protective of health, particularly in the context of disaster. Fewer studies have explored the presence and impact of social support in rural Ecuador. This study engages a rural community in Ecuador to examine the general levels of social support, differences in social support based on different demographic groupings and relationships among social support and health outcomes and protective health behaviors. Methods: A cross-sectional design was used to survey 416 people in a rural Ecuadorian community that had recently experienced an earthquake. Spanish-language versions of the Multidimensional Scale of Perceived Social Support and the Interpersonal Support Evaluation List-12 were applied, as well as questions about demographics and risk reduction behaviors. Body mass index, blood pressure, and cholesterol and blood sugar levels were assessed. Analysis of variance assessed differences in social support among demographic groupings, risk reduction behaviors, and health outcomes. Results: Levels of social support were moderate. Few statistically significant (ie p<0.05) differences in amount of social support received or in sources of social support were found. Men, people 80 years or older, divorced or widowed people, and people living in peripheral areas received less social support than women, people of all other ages, married/cohabitating people, and people living within the village, respectively. Effect sizes of these differences were small. No relationship between social support and health outcomes were found, and few were found for risk reduction factors. Conclusion: These findings indicate that social support may function differently in rural Ecuador than in urban contexts. Those promoting social support in rural communities may wish to focus on community-level, not individual-level, interventions. Limitations of applying an assessment of social support from urban Ecuadorian contexts to rural Ecuadorian contexts are discussed.